Pengaruh Aplikasi Beberapa Jenis Bahan Aktif Insektisida Sintetis terhadap Predator Eocanthecona furcellata (Wolff) di Laboratorium: english - Rustam, Rusli; Fauzana, Hafiz; Salbiah, Desita; Pamungkas, Nailul Hakim (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2019)
Application of various synthetic insecticides to control fire caterpillar (Setora nitens) on palm oil plantation has negative impact on predator Eocanthecona furcellata, the natural enemy of fire caterpillar. Profenofos, deltamethrin and cypermethrin insecticides have negative effect because they can reduce population of E. furcellata. The research was conducted using contact method with concentration of 2 ml.l-1 and water as a control with 7 days in observation time. Generallly, the result of the research showed that synthetic insecticides have toxicity on E. furcellata. The profenofos had an effect on the total mortality of E. furcellata up to 63.33%, cypermethrin up to 59.99% and deltamethrin up to 53.33%. The female significantly was more tolerant than male. It is necessary to choose suitable insecticide that are not only effective in controlling S. nitens but also safe for natural enemies.